Determinação de parâmetros genéticos em população de gonçalo-alves (Astronium fraxinifolium) através das características fisiológicas da semente - De Aguiar, Ananda Virgínia [UNESP]; Bortolozo, Fernando Rodrigo [UNESP]; De Moraes, Mario Luiz Teixeira [UNESP]; De Sá, Marco Eustáquio [UNESP] (My University, 2001)
Seeds of Astronium fraxinifolium (Anarcadiaceae) were collected in two years, and submitted to tests of seed germination and vigour (first count, aging and electric conductivity), in order to verify the potencial of conservation and if variations in the seed quality presented on association with genetic parameters. Coefficient of heritability in average (ĥm 2) were 0.91 and 0.97 to germination; 0.90 and 0.96 to first count; 0.93 and 0.97 to aging and 0.95 and 0.99 to electric conductivity, for seeds collected in 1997 and 1998, respectively, evidencing a great heritability to all studied characteristics. Genetic variability was influenced more by environmental conditions of blooming and harvest of seeds than storage time.
Determination of genetic parameters in a Astronium fraxinifolium population by seed physiological characteristics
Keywords: Astronium fraxinifolium; Genetic conservation; Germination; Seeds; Vigour; Electric conductivity; Genetic engineering; Physiology; Seed; Genetic Engineering; Heritability; Resistivity